Impact of solid fuel use on asthma prognosis and consistent peak expiratory flow changes: Evidence from China - Yuexi Chen; Shuojia Xie; Xirong Chen; Xiaowen Zhong; Linhang Yang; Weitong Lin; Junfeng Huang; Ruchong Chen (Ecotoxicology and Environmental Safety)
Background: Exposure to solid fuels might result in substantial indoor air contamination that can detrimentally affect respiratory wellness. Yet the connection between use of such fuels and the incidence as well as the progression of asthma needs further clarification. This investigation endeavors to conduct an integrative cross-sectional and longitudinal study to examined the link between solid fuel utilization and asthma. Methods: Involving participants from the China Health and Retirement Longitudinal Study (CHARLS), this research scrutinized the impact of solid fuel exposure on asthma incidence, peak expiratory flow (PEF), and mortality in asthma patients. The study applied logistic and linear regression for the cross-sectional data, Cox proportional hazards models and linear mixed effects methods were utilized to gauge the impact on mortality and PEF among subjects with asthma. Results: Among the 12025 individuals surveyed, use of solid fuels was significantly associated to increased asthma risk and a decrease in PEF among the Chinese population (P < 0.001), with consistent trends noted across categories of age, gender, and smoking habits. The survival analysis demonstrated that, when contrasted with non-asthmatic individuals using cleaner fuel, the risk of all-cause mortality was 1.63 times higher (95 % CI = 1.33, 2.00, p < 0.001) in asthmatic individuals regularly using solid fuels. Mixed-effects model pointed to a statistically potential interaction between gender and the influence of solid fuels on long-term reduction in PEF in patients with milder asthma forms. Conclusions: The research provided insights into the harmful effects of solid fuel dependence on asthma risk and outcomes, contributing novel evidence supporting this link. The results emphasize the necessity of curtailing solid fuel use to diminish potential health risks associated with asthma and to improve prognosis in affected individuals.